The Impact of The Raise Fuel Oil Price (Diesel Fuel) to Activities of The Catching of Fishermen Landed The Catch In PPS Bungus West Sumatra ( Cases: Lift Net Fishermen21 GTand 30 GT). - Muhammad Daiyuddin; Hendrik '; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in June 2015 which is located in PPS Bungus the Province of West Sumatra. Research aims to analyze changed fishing ground, time of fishing and fishing frequency, the operational cost which issued, and income the owner and crew members a lift net ship 21 GT and 30 GT with the rising fuel oil prices (diesel fuel). The method used in this research is a case study. The diesel fuel prices used in this research are Rp 6.900,-/litres and Rp 6.900,-/litres.The result showed that the price of diesel fuel oil does not cause changed fishing ground, time of fishing and fishing frecuency so that the number of diesel fuel (litres) and ice (stem) used the lift net fishermen also unchanged. However, the increase in the price of diesel is causing a rise in operating costs of lift net ship 21 GT, an average of Rp 117.000,-/trip (7,8 %) and the lift net ship 30 GT, an average of Rp 616.000,-/trip (7,0 %). Trip catching lift net ship done for 5 days, so that in one day lift net fishermen 30 GT increased operational cost an average of Rp 123.200,-/day. On the other side, the increase in operating costs due to rising diesel prices led to a decrease in revenues of each fisherman. Lift net fisherman with ship 21 GT decreased average income of Rp 58.500,-/trip (11,9%) for each fisherman crew and owner. Meanwhile, lift net fishermen 30 GT decreased average income of Rp 308.000,-/trip (10,6%), or an average of Rp 61.600,-/day.Keywords: impact, fuel oil price increases, diesel fuel, cost, income